AMELIORASI BAHASA BATAK TOBA - Erlindo Berliana; Auzar Auzar; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Amelioration is a change of meaning which results in a new meaning perceived as better value than the old meaning (raising meaning). The purpose of this research is to describe amelioration Batak Toba language. This type of research is qualitative research. In this study the author uses descriptive method. Descriptive method is a method that is done with the steps as follows: data collection, classifiers, analyze, and make conclusions to get a picture of the object. The source of this research is the corpus 1) folklore, 2) the maxim, 3) the sermon, and 4) the daily speech of the Batak Toba community. The data containing amelioration is then recorded and transcribed. Technique of collecting data that is using technique refer to. Result of research, found four form of amelioration in Toba Batak language which amount to 89 data. The division of the form is (1) amelioration and synonym of word form of 72 data, (2) phrase amelioration, synonymous with rough word meaning of 13 data, (3) amelioration and synonym in phrase form and (4) amelioration of word form, synonymous with the form of meaningful rough phrases amounting to 2 data.Keywords: Amelioration, Batak Toba Language